2023
DOI: 10.3390/nu15153393
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Based Dairy Alternatives Contribute to a Healthy and Sustainable Diet

Winston J. Craig,
Virginia Messina,
Ian Rowland
et al.

Abstract: Plant-based foods are increasing in popularity as more and more people are concerned about personal and planetary health. The consumption of plant-based dairy alternatives (PBDAs) has assumed a more significant dietary role in populations shifting to more sustainable eating habits. Plant-based drinks (PBDs) made from soya and other legumes have ample protein levels. PBDs that are appropriately fortified have adequate levels of important vitamins and minerals comparable to dairy milk. For the PBDs examined, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Furthermore, veganism (an exclusively plant-based diet) is a growing dietary/ lifestyle choice, with increasing sales of vegan products across the UK and North America (Sexton et al 2022). For these reasons, as well as those related to personal and planetary health (Craig et al 2023), plant-based dairy-milk alternatives have become common, including derivatives of soya, rice, oat, and various nuts. Soya-based beverages are the among the most popular and well-researched plant-based milk-alternatives (Hidalgo-Fuentes et al 2024), having been used as a milk-alternative for at least 2000 years (Sethi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, veganism (an exclusively plant-based diet) is a growing dietary/ lifestyle choice, with increasing sales of vegan products across the UK and North America (Sexton et al 2022). For these reasons, as well as those related to personal and planetary health (Craig et al 2023), plant-based dairy-milk alternatives have become common, including derivatives of soya, rice, oat, and various nuts. Soya-based beverages are the among the most popular and well-researched plant-based milk-alternatives (Hidalgo-Fuentes et al 2024), having been used as a milk-alternative for at least 2000 years (Sethi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The surge in vegan milk alternatives, driven by the increasing prevalence of dairy allergy and lactose intolerance (Rangel et al, 2016), is also fueled by ethical and environmental considerations (Leitzmann & Keller, 2020). Numerous life cycle analyses highlight the substantial environmental impact of dairy, making it scoring highest in most categories studied (Craig et al, 2023;McClements et al, 2019). The land required for animal protein is 6-17 times greater than for soy protein (Reijnders & Soret, 2003), and water use for oat and soy drinks is only 1.3% and 0.5%, respectively, compared to cow's milk (Craig et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous life cycle analyses highlight the substantial environmental impact of dairy, making it scoring highest in most categories studied (Craig et al, 2023;McClements et al, 2019). The land required for animal protein is 6-17 times greater than for soy protein (Reijnders & Soret, 2003), and water use for oat and soy drinks is only 1.3% and 0.5%, respectively, compared to cow's milk (Craig et al, 2023). This results in a carbon footprint 3.3 times greater for dairy than that of soy drinks (Craig et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature provides poor objective evidence on the effect of nutritional programs alone or in combination with the recommended phyto-derived food supplements (PDFSs) to facilitate dietary rebalancing [15,16]. Nevertheless, the benefits of human clinical trials using PDFSs have been reported [17][18][19][20][21][22][23][24][25], including improved well-being, loss of body weight, better lipid profile, fewer osteoarticular complaints, lower blood pressure, lower glycemic levels, and reduced respiratory insufficiency and cardiovascular risk. Some of these factors are directly associated with weight control and improved cholesterol profiles [26].…”
Section: Introductionmentioning
confidence: 99%